Overshoot‐free nonholonomic source seeking in 3‐D. (14th March 2017) - Lin, Jinbiao; Song, Shiji; You, Keyou; Krstic, Miroslav
Summary: This paper studies the problem of steering a nonholonomic vehicle with a constant forward velocity to localize a source in 3‐D. Of two existing 3‐D source‐seeking strategies, one causes overshoots of the vehicle around the source while the other shows slow convergence rate in approaching the source. We propose a composite of these 2 control strategies to achieve a balanced performance by taking advantage of both strategies. Moreover, we prove local exponential stability for a static spherical signal map using averaging and describe the influence of the parameters using root locus method. Simulation results further validate the effectiveness and advantages of the combined strategy.